The Ustasha Genocide Over the Serbs – the Continuing dolus specialis - Rakić, Branko (Napredak, 2022)
The key characteristic of the criminal aspect of the genocide, which distinguishes it from other violations of international humanitarian law and raises it to the level of the “crime above all crimes”, is the existence of the so-called genocidal intention of “complete or partial destruction of a specific national, ethnic, racial or religious group”. The gravity and monstrosity of the content of such intention, as q rule, require that it is deeply rooted in the conscience of the members of the group perpetrating this crime, while such inveteracy also implies the permanence of the intention, or genocidal idea. During World War II, the Serbian people, together with Jews and Romas, in the Independent State of Croatia were the victims of the genocide, the crime that abhorred even the Nazis. The idea and intention of the extermination of the Serbian people from the territory considered as Croatia’s national territory by the Croatian nationalists, although existing for centuries in the past, got its “theoretical formation” in the 19th century, primarily in the works of Ante Starčević, who was called the “Father of the Fatherland” while he was still alive. The Ustasha openly showed their enthusiasm and inspiration by Starčević’s works during World War II, claiming that there would not have been the Independent State of Croatia if it had not been for Starčević. The Ustasha ideology persisted after World War II, primarily through the activities of the Ustasha emigrants, but Croatian nationalism, open to accept the Ustasha ideological legacy, also persisted in the territory of Croatia itself. At the end of the 1980s and the beginning of the 1990s, the revival of the idea about the secession of Croatia and its realization also led to the revival of the idea of the Serbs as a “destructive factor” in Croatia and the necessity of their elimination from that territory. Tuđman’s Croatia resumed the Ustasha ideology in all its elements, including its attitude towards the Serbs and the genocidal intention, which had been largely realized during World War II. Drawing on the experience from the ISC, the Serbs became organized and prevented the repetition of the fate of their ancestors and relatives killed during World War II, but did not succeed in avoiding the “ethnic cleansing” from the territory of Croatia. The manner in which today’s Croatia interprets events both from World War II and from the 1990s shows that the Ustasha ideology is still deeply rooted in the significant element of the Croatian society, including practically the entire top government of Croatia. An essentially important element of the Ustasha ideology is its genocidal intention towards the Serbs still living in Croatia.